Disability Screening and Labor Supply: Evidence from South Africa - Mitra, Sophie (American Economic Review, 2009)
Yet research that examines the poverty reduction and labor supply effects of disability programs has taken place exclu-sively in developed countries with relatively low unemployment and high labor force participa-tion rates. In developing countries with high unemployment rates, the disincentive effect of cash transfers on labor supply has often been assumed to be economically insignificant (Anne Case and Angus Deaton 1998). In this paper, I provide initial evidence on, and draw attention to, the effect of the South Africa Disability Grant (DG) program on labor supply, in the context of a policy change in disability screening. I use a difference-in-differences estimator to assess the effect of a change toward a less intensive dis-ability screening on labor force nonparticipation for older individuals.If screening for disability benefit programs were perfect, the supply of disability benefits would be independent of labor supply decisions, and only those unable to work due to health con-ditions would receive benefits. However, the dis-ability screening process is imperfect because it is, in practice, difficult to determine whether a person is able to work, which is the typical test of eligibility for disability benefit programs. Recent evidence suggests that the work disincen -tive effects of disability benefits are expected to